(Non-)Inclusive Language in the Spanish Criminal Code: analysis and proposal - Rodríguez-Vázquez, Rosalía (2024)
Inclusive language is the type of language that uses a range of grammatically sound formulae to encourage a vision of the world in which both women and men are included in order to overcome linguistic sexism and androcentrism. The consistent use of inclusive language de-masculinises job-market realities that have traditionally been dominated by males, as is the case of the legal professions.In Spain, the legalfield haschangeddrastically in the last decades, to the extent that more than half ofthe judges and magistratesin the countryare female. Despite that, the legal codes on which sentences are based have not evolvedwith regardtothe use of inclusive language.This paperpresentsthe results of thesystematic analysis of gender-marked lexicon in the Spanish CriminalCode(1995, last modified2023). The quantitative and qualitative analysis of the Code allowsus to draw some conclusions regarding a) the overwhelming presence of non-inclusiveor gender-biased terms, and b) the frequency of use of each of those termsand its implications.The data obtained indicate that the Spanish Criminal Code is biased for gender inasmuch as it resorts to masculine formsin almost 100% of the cases. As a feasible alternative, this article introducessome language suggestions to make the CriminalCode moreneutraland inclusive.